2005
DOI: 10.1158/1078-0432.ccr-04-1535
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection of Early-Stage Laryngopharyngeal Squamous Cell Carcinomas

Abstract: We sought to determine whether early-stage laryngopharyngeal squamous cell carcinomas (SCC) can be detected through molecular analysis of exfoliated cells collected with the use of a pharyngoesophageal brush (PEB). Experimental Design:Thirty-three patients with a single, untreated, early-stage (T1orT2) SCC of the supraglottic larynx or pharynx underwent collection of cells with a PEB, followed by endoscopic biopsy of the tumor. PEB specimens were also collected from five healthy subjects. PEB samples and tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…This setup reduces sample handling and thus the risk of PCR contamination. In previous studies, 25-50% of HNSCCs showed abnormalities in D7S1482 (Coulet et al, 2000;Temam et al, 2005). In one of these studies, the majority of the mutations observed were insertion mutations (Coulet et al, 2000).…”
Section: Discussionmentioning
confidence: 91%
“…This setup reduces sample handling and thus the risk of PCR contamination. In previous studies, 25-50% of HNSCCs showed abnormalities in D7S1482 (Coulet et al, 2000;Temam et al, 2005). In one of these studies, the majority of the mutations observed were insertion mutations (Coulet et al, 2000).…”
Section: Discussionmentioning
confidence: 91%
“…P16 methylation is a frequent event in laryngeal carcinoma and was detected in more than 80% of the squamous cell cancer of the larynx [62]. Recently, it is demonstrated that methylation of p16 is an early event in squamous cell carcinoma at the laryngopharyngeal region, implying that methylated p16 may have a clinical value in screening patients with early laryngeal carcinoma [63]. Koscielny et al proposed that methylated p16 had prognostic value in a follow-up period of 3 years [64].…”
Section: Epigenetic Alterations In Human Malignanciesmentioning
confidence: 99%
“…Improper methylation status of the following genes has been identified thus far in laryngeal cancer: Retinoic acid receptor β (RARβ), death-associated protein kinase (DAPK), cyclin-dependent kinase inhibitor 2A (CDKN2A), MGMT, RASSF1A, fragile histidine triad, chromodomain-helicase-DNA-binding protein 5, cellular retinol binding protein 1 and HIC1 (12)(13)(14)(15)(16)(17)(18)(19). The majority of the studies reported certain correlations between the clinical course of the disease and the molecular changes identified.…”
Section: Discussionmentioning
confidence: 99%